Drug–Drug Interactions Between PA-824 and Darunavir Based on Pharmacokinetics in Rats by LC–MS-MS. (24th January 2018) - Wang, Libin; Zhao, Jun; Zhang, Ruitao; Mi, Le; Shen, Xin; Zhou, Nan; Feng, Tian; Jing, Juan; Liu, Xueying; Zhang, Shengyong
Abstract: Currently, patients with co-infection with HIV and tuberculosis are treated with more than one drug. PA-824 a new chemical entity and a member of a class of compounds known as nitroimidazo-oxazines, has significant antituberculosis activity and a unique mechanism of action. Darunavir (Prezista TM ) is a new protease inhibitor of HIV-1. A simple, sensitive and rapid LC–MS-MS method has been developed and validated for simultaneous determination of PA-824 and darunavir. Chromatographic separation was achieved on Agilent Eclipse plus C18 column (100 mm × 2.1 mm, 3.5 μm) using gradient elution of acetonitrile–water (90:10, v / v ) with fast gradient elution at a flow rate of 0.6 mL/min and run time of 4.5 min. The mass spectrometer was run in positive electrospray ionization mode using multiple reaction monitoring to monitor the mass transitions. The method was validated for accuracy, precision, linearity, range, selectivity, lower limit of quantification, recovery and matrix effect. All validation parameters met the acceptance criteria according to regulatory guidelines. The method had been successfully applied to a pharmacokinetic study of fixed dose administration of PA-824, darunavir and their combination in rats. The results indicated that when co-administration of darunavir could decrease the amount of PA-824 in vivo and extend the elimination half-life.